PENINGKATAN HASIL BELAJAR MATEMATIKA METODE FUN TEACHING PADA SISWA KELAS IV SD NEGERI 163095 - Sintaria Sintaria (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
This aim of this research is to improve learning result on mathematic subject  through fun teaching method. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class IV, SDN 163095 Tebing Tinggi which amounted to 36 students. This study used a qualitative descriptive analysis technique. Based on data obtained from the measurement of the student learning outcomes on the cycle I of 80,55 % and cycle II amounted to 97,22 % note there is an increase in student learning outcomes. This means learning the mathematic using fun teachingmethod can improve learning outcomes in class IV SDN 163095 Tebing Tinggi.Key word :Fun Teaching, Learning Result, Mathematic